Translation and validation study of Quality of Life Questionnaire for Physiological Pregnancy at Sandeman Provincial Hospital, Quetta, Pakistan - Rabia Ishaq; Aiesha Ishaque; Qaiser Iqbal; Faisal Shahzad; Nafees Ahmed; Fahad Saleem (Journal of the Pakistan Medical Association, 2021)
Objective To examine the psychometric properties of the Urdu version of the Quality of Life Questionnaire for Physiological Pregnancy (QOL-GRAV). Methods This cross-sectional study was conducted at the Obstetrics, Gynecology department of Sandeman Provincial Hospital, Quetta. The QOL-GRAV was translated into Urdu by using a forward-backward procedure. The test-retest reliability was assessed through Cronbach’s alpha reliability analysis. The validity of the translated questionnaire was constructed by using Exploratory Factor Analysis (EFA) through principal axis factoring extraction and Oblique rotation with Kaiser Normalization. SPSS v 20.0 was used for data analysis with p<0.05 as significant. Results The Urdu version of the questionnaire (QOL-GRAV-U) exhibited acceptable alpha values of 0.780 (Test) and 0.812 (Retest) at two-time points with an overall value of 0.790 (field test). All items of the QOL-GRAV-U showed good stability with Intraclass Correlation Coefficient values of > 0.80. The Kaiser-Meyer-Olkin measure of sampling adequacy for the factor analysis was 0.812. Barlett’s Test of Sphericity was significant (Chi-square = 1032.43; p < 0.05) revealing relationships of the data and suitability of EFA. Three factors explaining the total variance of 65% were extracted whereby loading values for all nine constructs were acceptable (> 0.40). Conclusion The results of this study conclude that the translated version of QOL-GRAV-U is a valid and reliable instrument for the assessment of QoL for pregnant women in regions where Urdu is a prime language of communication. Continuous....